Keterampilan Proses Fisika Siswa Melalui LKS Berbasis Jelajah Alam Sekitar (JAS) Pada Materi Pokok Suhu dan Kalor Di SMAN 2 XIII Koto Kamparâ€. - Danis, Rahma Danis; ', Azhar; ', Syahril (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstrak: The purpose of this study was to describe the results of the physics students learn the skills and know the difference between the skills students learn physics processes using worksheets based natural learnig (JAS) with students who learn using worksheets conventional. The research was conducted from February 2015 through June 2015 with a population of class X IPA and sample class X IPA 25 students and XIPA 2, 24 students. The design of this research is a form of pre-experimental design intact-group comparison. Instruments used test results of students' learning skills physics process which comprises 12 multiple choice questions. Data collection techniques in research is the provision of test results of physical processes of learning skills of students. Technical analysis of data used descriptive analysis and inferential analysis. Descriptive analysis of the average absorption of 80% class experiment with both categories while the control group was 74% in both categories. Based on the absorption of students it can be said the effectiveness of learning in the experimental class and control class is effective. Classical mastery learning students in the experimental class is 84% â€‹â€‹complete and 62.5% control class is declared incomplete. Classical completeness indicators of process skills in the experimental class that is 100% complete and incomplete control class is 75%. Inferential analysis through statistical calculation t test SPSS 16. tcount = 2.1667 and ttable = 2.012. Based on the criteria of hypothesis testing tcount> ttable so that there is a significant difference against worksheets skills through a process physics-based Natural base learning Around with worksheets conventional level of 95%. Keywords: process skills, Nature-Based Learning (JAS), Worksheets, Temperature and Heat.